Protected area branding strategies to increase stewardship among park constituencies - King, Lisa; McCool, S.; Fredman, P.; Halpenny, E. (IUCN, 2012)
With the complexity and resource intensity needed to manage parks, protected area managers increasingly rely on their constituencies to assume stewardship responsibilities. To meet the intentions of the Convention on Biodiversity Target 11, thousands of new protected areas will need to be gazetted. This dramatic increase in the number of global protected areas will significantly add to the dependence of managers on their constituencies to be actively engaged in park protection and management. One underutilized management tool to connect people to parks sustainably is branding. Protected area brands can engage emotions, evoke personal beliefs and prompt the behaviours managers prefer when the brand’s core values are appropriately expressed. Yet, management often does not wield these brands to their maximum potential, thus limiting the tangible and intangible benefits they could bestow if simple marketing practices were followed. This paper outlines three fundamental branding practices – building brand awareness, teaching brand meaning and growing positive brand equity over time – that are applicable to the goals of every protected area manager. Strategically deployed, branding plays an essential role in the sustainability of parks and protected areas.